Oral potentially malignant disorders: A consensus report from an international seminar on nomenclature and classification, convened by the WHO Collaborating Centre for Oral Cancer. (26th November 2020) - Warnakulasuriya, Saman; Kujan, Omar; Aguirre‐Urizar, José M.; Bagan, José V.; González‐Moles, Miguel Ángel; Kerr, Alexander R.; Lodi, Giovanni; Mello, Fernanda Weber; Monteiro, Luis; Ogden, Graham R.; Sloan, Philip; Johnson, Newell W.
Abstract: Oral potentially malignant disorders (OPMDs) are associated with an increased risk of occurrence of cancers of the lip or oral cavity. This paper presents an updated report on the nomenclature and the classification of OPMDs, based predominantly on their clinical features, following discussions by an expert group at a workshop held by the World Health Organization (WHO) Collaborating Centre for Oral Cancer in the UK. The first workshop held in London in 2005 considered a wide spectrum of disorders under the term "potentially malignant disorders of the oral mucosa" (PMD) (now referred to as oral potentially malignant disorders: OPMD) including leukoplakia, erythroplakia, proliferative verrucous leukoplakia, oral lichen planus, oral submucous fibrosis, palatal lesions in reverse smokers, lupus erythematosus, epidermolysis bullosa, and dyskeratosis congenita. Any new evidence published in the intervening period was considered to make essential changes to the 2007 classification. In the current update, most entities were retained with minor changes to their definition. There is sufficient evidence for an increased risk of oral cancer among patients diagnosed with "oral lichenoid lesions" and among those diagnosed with oral manifestations of 'chronic graft‐versus‐host disease'. These have now been added to the list of OPMDs. There is, to date, insufficient evidence concerning the malignant potential of chronic hyperplastic candidosis and of oral exophytic verrucous hyperplasia to consider these conditions as OPMDs. Furthermore, due to lack of clear evidence of an OPMD in epidermolysis bullosa this was moved to the category with limited evidence. We recommend the establishment of a global research consortium to further study the natural history of OPMDs based on the classification and nomenclature proposed here. This will require multi‐center longitudinal studies with uniform diagnostic criteria to improve the identification and cancer risk stratification of patients with OPMDs, link them to evidence‐based interventions, with a goal to facilitate the prevention and management of lip and oral cavity cancer.